Information security culture a human firewall approach - Omar Zakaria (LAP Lambert Academic Pub., 2013)
In order to ease on such establishment, his book introduces several principles, in which can help to guide employees on their responsibilities and roles. These principle can also be used as a human firewall to combat any threats caused by insiders. In short, implementation of such principles can help to encourage all employees to practise information security responsibilities rather than to delegate them to technical personnel alone. This book is intended to change the employees' current security perception from "they" are responsible to "all of us" are responsible with regards to information security practices within an organisation.